Cariotipo de Peromyscus grandis (Rodentia: Criceidae) - Ordóñez-Garza, Nicté; Swier, Vicki J.; Hanson, John D.; Sotero-Caio, Cibele G.; Bradley, Robert D. (THERYA, 2013)
Peromyscus grandis is a rodent whose distribution is restricted to the mountain ranges of central Guatemala. This note represents the first report of karyotypic data for this species. The karyotype (fundamental number = 58) closely resembles karyotypes of other species ofPeromyscus. Key words: chromosomes, Cricetidae, endemic, karyogram, Peromyscus mexicanus group.